INDUKSI KALUS JARAK PAGAR (Jatropha curcas L.) PADA MEDIA MS DENGAN PENAMBAHAN BERBAGAI KONSENTRASI BAP (Benzyl Amino Purin) DAN 2,4-D (Dichlorophenoxy Acetic Acid) - Haryati Baktiar; Muslimin Muslimin; I Nengah Suwastika (Biology Department, Mathematics and natural science, Tadulako University, 2017)
This research was conducted from January to June 2015 at the Tissue Culture Laboratory, Faculty of Forestry, Tadulako University. The explant used in this study was the stem of seedling. Experimental was based on a completely randomized design (CRD) with 4 treatments, and 3 replication, with 3 explants on each unit. Growth Medias as treatments were H1 = MS0 + 0.5ppm BAP + 1.5 ppm 2.4-D; H2 = MS0 +0.5 ppm BAP + 2 ppm 2.4-D, H3 = MS0 + 0.5 ppm BAP + 2.5ppm 2.4-D, andH4 = MS0 + 0.5 ppm BAP + 3ppm 2.4-D. Parameters observation were time in callus appear, type of callus, color of callus, the weight of callus, morphology of callus cells. Callus was induched on those medium under dark condition at 26-280 C. The result of the research showed that all treatments can induced the callus. The Medium of ms0 + 0,5ppm BAP + 1.5 ppm of 2,4-D (H1) was the best media for callus induction, as it showed in short period of callus induction, the appearance of yellowish-white colors, highest in mass and volume of the callus cell, and showed uniform and active cell in proliferation.